2020
DOI: 10.1038/s41746-020-00349-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance and clinical utility of supervised machine-learning approaches in detecting familial hypercholesterolaemia in primary care

Abstract: Familial hypercholesterolaemia (FH) is a common inherited disorder, causing lifelong elevated low-density lipoprotein cholesterol (LDL-C). Most individuals with FH remain undiagnosed, precluding opportunities to prevent premature heart disease and death. Some machine-learning approaches improve detection of FH in electronic health records, though clinical impact is under-explored. We assessed performance of an array of machine-learning approaches for enhancing detection of FH, and their clinical utility, withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…In our study, results showed that the three machine learning models had similar high predictive accuracy in classifying FH patients (accuracy > 99.00%). This is consistent with prior findings using a random forest algorithm in health data [19] and other prior findings using random forest, gradient boosting, deep learning and ensemble learning algorithms in primary care data [28]. The decision tree model outperformed the other machine learning models, with the highest accuracy to determine the likelihood of FH.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, results showed that the three machine learning models had similar high predictive accuracy in classifying FH patients (accuracy > 99.00%). This is consistent with prior findings using a random forest algorithm in health data [19] and other prior findings using random forest, gradient boosting, deep learning and ensemble learning algorithms in primary care data [28]. The decision tree model outperformed the other machine learning models, with the highest accuracy to determine the likelihood of FH.…”
Section: Discussionsupporting
confidence: 89%
“…Validation and implementation of practicable systematic screening approaches is an important challenge that needs to be addressed. Akyea et al (2020) recently published results on a diagnostic approach using machine-learning (ML) algorithms, offering a new method (in addition to standard prediction modelling) with a high accuracy in detecting FH in adults. (38) However, these results cannot be directly applied to children, which would be the optimal age group for FH screening.…”
Section: Discussionmentioning
confidence: 99%
“…Akyea et al (2020) recently published results on a diagnostic approach using machine-learning (ML) algorithms, offering a new method (in addition to standard prediction modelling) with a high accuracy in detecting FH in adults. (38) However, these results cannot be directly applied to children, which would be the optimal age group for FH screening. VRONI collects baseline and long-term follow-up data of children with FH and their affected relatives, covering clinical data in form of dedicated questionnaires and health records, laboratory parameters as well as genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…For example: the FIND FH model. This model recognizes the clinical phenotype for familial hypercholesterolemia and provides the framework for a HIPAA-compliant method to contact these identified individuals with FH [33][34][35][36].…”
Section: Diagnosis Of Familial Hypercholesterolemiamentioning
confidence: 99%